Diversity Induction of Dendrobium sylvanum Orchid through In Vitro Irradiation of Gamma Ray - Eka Puji Lestari; Ahmad Yunus; Sugiyarto Sugiyarto (Biosaintifika: Journal of Biology & Biology Education, 2018)
Dendrobium sylvanum orchid is categorized as lowland habitus orchid and able to survive wihtout any shade. Orchid cultivation takes a very long time so it needs faster cultivation and producing large quantities. Therefore, it is necessary to do orchid culture by using tissue culture processes and then given gamma ray irradiation to bring up new characters in the orchid .The purpose of this research was to discover the impact of gamma ray irradiation in vitro to the diversity of D. sylvanum. The doses of gamma ray used in this research were 0 Gy, 15 Gy, 30 Gy, 45 Gy, and 60 Gy. The results obtained indicated that mutation mostly occurred on the treatment with 15 Gy (4.4 cm of plant height, 2.67 of leaves, 2.36 cm of leaf length, 0.49 cm of leaf width, and 5.33 of root strands) compared to the other doses and the control plants. The new finding in this research is the gamma ray dose that can optimally stimulate the mutation in D. sylvanum. This information is useful to generate the new variety in orchid cultivation in Indonesia. This research provides innovation in orchid cultivation and new variety that is possible to arise after the mutation.